2016
DOI: 10.1534/g3.116.030080
|View full text |Cite
|
Sign up to set email alerts
|

Cilia-Associated Genes Play Differing Roles in Aminoglycoside-Induced Hair Cell Death in Zebrafish

Abstract: Hair cells possess a single primary cilium, called the kinocilium, early in development. While the kinocilium is lost in auditory hair cells of most species it is maintained in vestibular hair cells. It has generally been believed that the primary role of the kinocilium and cilia-associated genes in hair cells is in the establishment of the polarity of actin-based stereocilia, the hair cell mechanotransduction apparatus. Through genetic screening and testing of candidate genes in zebrafish (Danio rerio) we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(68 citation statements)
references
References 98 publications
4
63
0
Order By: Relevance
“…Stereocilia labeling is consistent with transit through MET channels reported to be in the stereocilia, but why kinocilia labeling occurs is unclear at this time. Notably, recent work shows that mutations in several kinocilia proteins affect AG toxicity (37). Following appearance in the apical HC extensive.…”
Section: Resultsmentioning
confidence: 99%
“…Stereocilia labeling is consistent with transit through MET channels reported to be in the stereocilia, but why kinocilia labeling occurs is unclear at this time. Notably, recent work shows that mutations in several kinocilia proteins affect AG toxicity (37). Following appearance in the apical HC extensive.…”
Section: Resultsmentioning
confidence: 99%
“…One, ift88, is believed to be resistant to hair cell death in 175 response to the aminoglycoside neomycin due to reduced neomycin uptake as a result 176 of reduced mechanotransduction activity. The other, cc2d2a, appears to have normal 177 neomycin uptake and mechanotransduction activity (Stawicki et al, 2016). We found 178 reduced hair cell death in response to cadmium in ift88 mutants ( Figure 3A), further 179…”
Section: Acute Cadmium Treatment Can Kill Hair Cells Of Larval Zebrafmentioning
confidence: 65%
“…Mutations in one of those genes, ift88, did lead to resistance in 297 cadmium-induced hair cell death similar to what had previously been seen with 298 aminoglycosides. These mutants have previously been shown to have a decrease in 299 FM1-43 uptake (Stawicki et al, 2016) and a decreased response to water jet stimulation 300 (Kindt et al, 2012), suggesting impaired mechanotransduction activity though 301 mechanotransduction is not eliminated as in cdh23 mutants where no response is seen 302 (Nicolson et al, 1998). Thus, ift88 mutant's resistance to cadmium-induced hair cell 303 death further supports the role of mechanotransduction in this process.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Ubiquitous transgenic expression of a GFP-tagged murine Arl13b protein in the zebrafish, whilst labelling most cilia very effectively (Borovina et al, 2010), also increases their length, and is reported to disrupt both ciliary motility and otolith formation in the ear (Lu et al, 2015). Mutation of arl13b results in shorter lateral line kinocilia; cilia in the ear were not examined (Stawicki et al, 2016). Cilia in all tissues, including the ear, are missing in maternal-zygotic mutants for the IFT-B gene ift88 (Huang and Schier, 2009) Different ciliary types in the zebrafish ear also have different genetic requirements for some gene products.…”
Section: Length Control Of Cilia In the Zebrafish Ear And Lateral Linementioning
confidence: 99%